Higher Than the Original Stands the Translation: Translating Heidegger into Filipino - Barbaza, Remmon E (Archīum Ateneo, 2013)
This paper is a reflection on the author’s experience of translating Martin Heidegger into Filipino. It first addresses the questions of principles underlying the act of translation, such as those of fidelity (to both source and target languages, original author and translator), as well as the role of the translator as an intermediary between the original author and the readers. Then it demonstrates examples of his experience of translating selected key terms and passages in Heidegger—such as sein, stellen, Ereignis, and their cognates—indicating the difficulties as well as the challenges that arise in the work of translation. A notable problem or challenge is the absence in Filipino (as in other Austronesian languages) of the verb “to be,” one of the most important subjects of philosophical inquiry in the Western tradition. It ends by reflecting on this experience of translation, noting how even the German concept of Übersetzen and that of the Filipino salin may lend themselves to a “fusion of horizons,” and how, in the Heideggerian sense, translation may be said to stand higher than the original.